Migration Aspirations and Intentions - Matthias Huber; Till Nikolka; Panu Poutvaara; Ann-Marie Sommerfeld; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2022)
We carried out two multinational surveys to analyze aspirations and intentions to emigrate, and how these are linked to each other. One survey covered language course participants in 14 countries, and another students in 6 countries. We identify two groups that have been largely neglected in previous research on migration aspirations and intentions: those who intend to migrate permanently without aspirations to do so and those who intend to migrate temporarily. Analyzing main motivations to emigrate shows that discrepancy among women is driven mainly by family, and among men by work and studies.
Keywords: F22; D91; J16; 330; international migration; migration choice; temporary migration; permanent migration; aspirations; intentions; multinational survey